Quantifying Jump Height Using Markerless Motion Capture with a Single Smartphone - Timilehin B. Aderinola; Hananeh Younesian; Darragh Whelan; Brian Caulfield; Georgiana Ifrim (IEEE Open Journal of Engineering in Medicine and Biology, 2023)
Goal: The countermovement jump (CMJ) is commonly used to measure lower-body explosive power. This study evaluates how accurately markerless motion capture (MMC) with a single smartphone can measure bilateral and unilateral CMJ jump height. Methods: First, three repetitions each of bilateral and unilateral CMJ were performed by sixteen healthy adults (mean age: 30.87 $±$ 7.24 years; mean BMI: 23.14 $±$ 2.55 $\text{kg/m}^{2}$ ) on force plates and simultaneously captured using optical motion capture (OMC) and one smartphone camera. Next, MMC was performed on the smartphone videos using OpenPose. Then, we evaluated MMC in quantifying jump height using the force plate and OMC as ground truths. Results: MMC quantifies jump heights with ICC between 0.84 and 0.99 without manual segmentation and camera calibration. Conclusions: Our results suggest that using a single smartphone for markerless motion capture is promising.